Fatigue life prediction of high-speed composite craft under slamming loads using progressive fatigue damage modeling technique. (January 2022) - Shabani, Peyman; Shabani, Nazanin
Highlights: A predictive fatigue damage modeling technique is developed to estimate the fatigue life of composite craft under slamming loads. This model can predict the fatigue damage sequences under arbitrary loading conditions. This model can be used in the design stage of composite crafts. By minimizing the number of required experiments, this model can be very cost-effective. Abstract: A reliable predictive method is developed based on the progressive fatigue damage modeling technique to estimate the fatigue life of high-speed composite craft. In this method, at each loading cycle, the occurrence of different failure types would be inspected and based on the failure type, either gradual or sudden degradation rules would be followed to update the material properties. This procedure continues until the final failure of the structure. To implement this method, a MATLAB code is developed based on material degradation rules which integrating with the Abaqus it can be used for complex geometries. This method enables us to predict the fatigue life of composite structures with different layup configurations under arbitrary loading conditions only by knowing the static and fatigue behavior of unidirectional laminates. To even more reduce the number of required tests, the energy-based unified fatigue life model is employed. Owing to the low number of required tests, this method can be very cost-effective in the design stage of composite structures that are intended to endure cyclic loads.